The Prosocial Outgrowth of Filial Beliefs in Different Cultures: A Conditional Mediation Model Analysis - Zheng, Wang; Guo, Qingke; Huang, Taian; Lu, Jianli; Xie, Chaoxiang (Frontiers in Psychology, 2021)
Filial piety is a concept originated from ancient China which contains norms of children’s feelings, attitudes, and behaviors toward their parents. The dual filial piety model (DFPM) differentiated two types of filial belief: reciprocal vs. authoritarian filial piety (RFP vs. AFP). Recent scholars suggest that the functions of filial piety may differ across cultures. This study examined the mediating effects of empathy, moral identity, gratitude, and sense of indebtedness in the relationship between filial piety and prosocial behavior (PB) and the moderating effects of nation. Questionnaires measuring filial piety, PB, moral identity, gratitude, and sense of indebtedness were administrated to Chinese and Indonesian participants. Moderated mediation modeling was conducted to analyze data. The results showed that empathy, moral identity, gratitude, and a sense of indebtedness have significant mediating effects in the association of filial piety and PB. And nation served as a moderator. (1) RFP could promote PB via enhanced empathy, moral identity, gratitude, and a sense of indebtedness, both among Chinese and Indonesian participants, while AFP did the same job only among Indonesian participants. (2) Among Chinese participants, AFP was not directly associated with PB, but was negatively associated with PB via reduced gratitude and a sense of indebtedness. (3) Nation (China vs. Indonesia) moderated the direct or indirect effect of RFP/AFP on PB, with RFP exerting stronger positive effects on outcome variables among Chinese (relative to Indonesian) participants and AFP exerting stronger positive effects on outcome variables among Indonesian (relative to Chinese) participants. These results showed that RFP can promote prosocial development by the cultivation of empathy, moral identity, gratitude, and a sense of indebtedness, regardless of whether the participants grew up in China or other cultural backgrounds. But the effect of AFP on PB was significantly conditioned by culture. This suggests that the function of RFP may be a cultural universal. However, the mechanisms that AFP influences PB can differ considerably across cultures. Findings of this study further indicate that filial piety beliefs may facilitate prosocial development in the ways conditioned by cultures.